2016
DOI: 10.1080/14656566.2016.1183648
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide for the treatment of ulcerative colitis

Abstract: Introduction Budesonide is a synthetic corticosteroid characterized by enhanced topical potency and limited systemic bioavailability. Its use in ulcerative colitis (UC) was limited to rectal preparations until recently when the new oral budesonide formulation incorporating the multi-matrix system technology was introduced. The purpose of this review is to evaluate the current role of oral and rectal budesonide in managing UC patients Areas Covered In this paper, we described the chemical structure and pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 61 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…This may be due to the scarce or contrasting literature produced until now in terms of RCTs for these second-generation steroids. It is noteworthy that while there is no direct comparison to systemic steroids for budesonide [51], the efficacy and safety of oral prolonged release BDP vs. oral PD is well established in a controlled trial [24], but data were published after guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the scarce or contrasting literature produced until now in terms of RCTs for these second-generation steroids. It is noteworthy that while there is no direct comparison to systemic steroids for budesonide [51], the efficacy and safety of oral prolonged release BDP vs. oral PD is well established in a controlled trial [24], but data were published after guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to this extensive first-pass metabolism, BDP has a limited impact on the HPA axis with fewer systemic effects than traditional CSs [52]. Interestingly, morning plasma cortisol levels seem to have a dose-dependent decrease in BDP and budesonide [30,51]. If confirmed, this does call into question whether the ‘second-generation’ of topically acting steroids have safety advantages with dosage higher than 5 mg/day compared to systemic CSs.…”
Section: Discussionmentioning
confidence: 99%
“…Budesonide is a nonabsorbable steroid acting locally in the small intestine. It has a low oral bioavailability due to high first pass hepatic metabolism (28). A preliminary trial showed that a 9-month treatment with budesonide is effective in patients with IgA nephropathy (29).…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Budesonide is an oral, synthetic glucocorticoid that undergoes extensive first-pass metabolism in the liver resulting in low systemic bioavailability while retaining a high degree of topical activity within the small bowel and colon 6. This allows for a potent, local glucocorticoid effect in the small bowel and colon while minimising the adverse effects seen with prednisone and other systemic glucocorticoid therapies, such as adrenal axis disturbances and loss of bone mineral density 6. While commonly used in inflammatory bowel disease, budesonide is very rarely used in CID.…”
Section: Introductionmentioning
confidence: 99%